Financial Performance Analysis Using the EVA Method at PT Indofood CBP Sukses Makmur Tbk for the 2021-2025 Period - Rhaisya Adellia; Almas Zaskia Nurlilahi; Tiara Eka Putri; Aura Septi Safana; Saharani Isabella; Aulia Elvira; Mutiara Zahwa; Yossinomita Yossinomita (P3M Politeknik Negeri Ambon, 2026)
This study aims to analyze the financial performance of PT Indofood CBP Sukses Makmur Tbk for the 2021-2025 period using the Economic Value Added (EVA) method. This study uses a descriptive quantitative approach with secondary data obtained from the company's annual reports. The analysis was conducted through the calculation of Tax Rate, Net Operating Profit After Tax (NOPAT), Invested Capital, Weighted Average Cost of Capital (WACC), Capital Charge, and EVA. The results show that ICBP's EVA was negative in 2021 by Rp90.3 billion, then positive in 2022 by Rp2,816.1 billion, in 2023 by Rp679.2 billion, in 2024 by Rp2,053.6 billion, and in 2025 by Rp612.4 billion. These findings indicate that ICBP was able to create economic value in four of the five years studied. However, EVA fluctuations indicate that increases in operating profit need to be balanced with capital cost control so that economic value creation can be sustained. Keywords: Financial Performance, Capital Charge, EVA, WACC, ICBP